The Problem of Notary Covernote As The Basis of A Bank In A Means of Financing or Credit In The Field of Banking - Azura, Audilia Hany; Akhmad Budi Cahyono (Jurnal Hukum dan Kenotariatan, 2023)
The notary's covernote itself is issued because the authentic deed relating to the bank credit disbursement process has not been completely completed by the notary, so the covernote is issued as a temporary legal umbrella while the process of making the authentic deed is completed by the notary. So the aim of this research is to find out the legal position of notary covernotes which are used as the basis for credit disbursement if they cause problems in the future and what the responsibilities of notaries are in issuing covernotes that are not regulated in statutory regulations. This research uses normative juridical research methods. The results of this research show that the practice of making covernotes by notaries is a habit carried out by notaries because creditors or banks want credit disbursement to be carried out so they need a basis for this so that making covernotes by notaries is not regulated by law and is not is a legal product from a notary which results in the absence of legal certainty in the covernote.